Accuracy of Fine Needle Biopsy (FNAB) in Lymph Nodes Tuberculosis - Sari, Aditya Sita; Kurniasari, Nila; Rahaju, Anny Setijo; Kusumastuti, Etty Hary; Rahniayu, Alphania (Health and Medical Journal, 2026)
Introduction: Tuberculosis (TB) is an infection caused by Mycobacterium Tuberculosis (Mtb) that can attack various organs such as peripheral lymph nodes. Fine needle aspiration biopsy (FNAB) is often used as one of the modalities of diagnosis of lymph node tuberculosis to determine the management of patients. Objective: The objective of this study is to evaluate the accuracy, efficiency, and effectiveness of FNAB in diagnosing lymph node tuberculosis. The findings will assess whether FNAB can be adopted as a standard diagnostic and management tool for patients with this condition. Methods: This is an observational analytic cross-sectional study in the population of patients with suspicion of lymph node tuberculosis at the Anatomical Pathology Unit of Dr. Soetomo General Academic Hospital Surabaya in one year period. FNAB examination was performed with Modified Grunwald Giemsa (MGG) and Ziehl Nielsen (ZN) staining to detect AFB (Acid Fast Bacilli) organisms, as well as PCR (Polymerase Chain Reaction) of peripheral blood. The results were analysed using Chi square statistic test. Results: The sensitivity, specificity, Positive Predictive Value (PPV) and Negative Predictive Value (NPV) of FNAB examinations were 100%, 33%, 59% and 100%, respectively, meanwhile the sensitivity and specificity of PCR peripheral blood examination were 8% and 70% compared to the ZN examination of the FNA aspiration material. Conclusion: FNAB had a higher sensitivity than PCR of peripheral blood to detect Mycobacterium Tuberculosis infection; on the other hand PCR of peripheral blood had a higher specificity than FNAB to detect Mycobacterium Tuberculosis infection.